PENGARUH KEBIJAKAN WAJIB SALAT BERJAMAAH TERHADAP ETOS KERJA PEGAWAI DAERAH KABUPATEN ROKAN HULU - Yuni Rafita; Wiwit Sylviana Agustin; Rizki Adhiputra; Siti Arni Wulandya; Hujair A.H. Sanaky (Millah: Journal of Religious Studies, 2014)
The authority of local Government become much broader since the autonomous region demanded that the officers of the Region to have a high work ethic. The establishment and reinforcement of the workethic is not solely determined by the quality of education or accomplishments that related to the profession and the world of work, but also on faith that could be grown through worship. Rokan Hulu, an area in Riau, has arule for the Muslim employees to prayer in congregation. This legislations was poured in the regulations of the Regents of Rokan Hulu at no. 18 in 2011 about the obligation for Muslim Employees to pray Zuhr and Asr in the Pasir Pengaraian mosque. This research aims to influence the policy of the employee’s work ethic. Data collection was conducted by questionnaire and interview. From the beginning hypothesis, there is a positive influence from mandatory prayer in congregation’s policy against employee’s work ethic. Data were analyzed using Descriptive Analysis and simple linear regression analysis. A descriptive analysis of the results shows that most of the employee of the Region agree with the policicy and optimist this policy will impact positively on work ethic. Using simple linear regression analysis showed that the policy of compulsory congregational prayersfor 0.843 give a positiveaffect to employee’s work ethic in Rokan Hulu. These results are supported by the statements of religious Activities Sekretriat Kasubag Area of Rokan Hulu, Mr. Damrah s. Sos, that the application of mandatory prayer in congregation policy Zuhr and Asr is a step to build the employee’s moralenvironment in order to avoid fraudulent practices which are currently evident.